Hospital epidemiology of abdominal adhesions - N. I. Ayushinova; I. A. Shurygina; M. G. Shurygin; E. G. Grigoryev (Acta Biomedica Scientifica, 2016)
The purpose of the research was to establish main causes of development and outcomes of adhesive obstruction. We analyzed the outcomes of treatment of 154 patients with acute intestinal obstruction. The following data were taken into consideration: age, gender, surgeries in past medical history, terms of adhesions manifestations, clinical symptoms, findings of additional examinations, methods of treatment, outcome. It has been established, that the most frequent causes of adhesions were appendectomy (23 %), stomach operations (21 %) and gynecological interventions (14 %). After surgeries performed in conditions of regional hospitals, adhesions developed after appendectomy, gynecological operations and interventions on the intestine. In patients operated in city hospitals intestinal obstruction more often occurred after extensive operations on the stomach, appendix, and after gynecological interventions. Urgent surgical interventions more often led to adhesive process in the abdominal cavity (63 %). Mortality made 5.8 %. Causes of death were intestinal fistulas and abdominal sepsis. Thus, acute adhesive intestinal obstruction as an extreme form of abdominal adhesions continues to be an urgent medical issue.